2009
DOI: 10.1007/s10570-009-9377-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of cotton gauze coating with microbial cellulose

Abstract: Microbial cellulose is a pure form of cellulose with widespread applications. It is very applicable for medical usage specially wound dressings due to its high liquid absorbency and hygienic nature. In this study, microbial cellulose formed/ coated on cotton gauze samples during its biosynthesis in a static medium (Hestrin & Scharm) for 6 days by Acetobacter Xylinium. Some essential factors of treated gauze samples, like water absorbency, drying time (water holding time), and amount of vertical wicking were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(59 citation statements)
references
References 29 publications
1
55
0
3
Order By: Relevance
“…Gelin et al have shown that only 10% of the 99 wt% water, which can be present in bacterial cellulose behaves like free bulk water. Also, a study by Meftahi et al showed that cotton gauze coating with microbial cellulose increases water absorbency and wicking ability over 30%, and reduces drying time significantly. These are very positive facts with respect to making bandages using BC‐containing materials.…”
Section: Resultsmentioning
confidence: 99%
“…Gelin et al have shown that only 10% of the 99 wt% water, which can be present in bacterial cellulose behaves like free bulk water. Also, a study by Meftahi et al showed that cotton gauze coating with microbial cellulose increases water absorbency and wicking ability over 30%, and reduces drying time significantly. These are very positive facts with respect to making bandages using BC‐containing materials.…”
Section: Resultsmentioning
confidence: 99%
“…Cellulose is widely utilized in industrial applications (textiles, dietary supplements, gauze, scaffolds for tissue regeneration, and even headphones) (72,73). Microbial cellulose is coveted because of its purity and is typically harvested from Gluconacetobacter xylinus (73,74).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Veloderm ® is a biological polymeric membrane (manufactured by BTC S.r.l., Ancona, Italy) composed of cellulose microfibrils that are characterized by a low polymerization degree and a high level of crystallinity. [3][4][5][6] Veloderm ® is a biological polymeric membrane (manufactured by BTC S.r.l., Ancona, Italy) composed of cellulose microfibrils that are characterized by a low polymerization degree and a high level of crystallinity.…”
mentioning
confidence: 99%